A Review on Dielectric Breakdown in Thin Dielectrics: Silicon Dioxide, High‐k, and Layered Dielectrics. (30th April 2019) - Palumbo, Felix; Wen, Chao; Lombardo, Salvatore; Pazos, Sebastian; Aguirre, Fernando; Eizenberg, Moshe; Hui, Fei; Lanza, Mario
Abstract: Thin dielectric films are essential components of most micro‐ and nanoelectronic devices, and they have played a key role in the huge development that the semiconductor industry has experienced during the last 50 years. Guaranteeing the reliability of thin dielectric films has become more challenging, in light of strong demand from the market for improved performance in electronic devices. The degradation and breakdown of thin dielectrics under normal device operation has an enormous technological importance and thus it is widely investigated in traditional dielectrics (e.g., SiO2, HfO2, and Al2 O3 ), and it should be further investigated in novel dielectric materials that might be used in future devices (e.g., layered dielectrics). Understanding not only the physical phenomena behind dielectric breakdown but also its statistics is crucial to ensure the reliability of modern and future electronic devices, and it can also be cleverly used for other applications, such as the fabrication of new‐concept resistive switching devices (e.g., nonvolatile memories and electronic synapses). Here, the fundamentals of the dielectric breakdown phenomenon in traditional and future thin dielectrics are revised. The physical phenomena that trigger the onset, structural damage, breakdown statistics, device reliability, technological implications, and perspectives are described. Abstract : As new dielectric materials are introduced in microelectronic devices, the electronic, physical, chemical, and thermal phenomena associated with the dielectric breakdown (which can produce the failure of the entire device) can also remarkably change. In this report, the dielectric breakdown process in traditional and two‐dimensional layered dielectrics is revised, making use of abundant statistical information extracted from sophisticated reliability tests.